Innovative Waste Management and Community Education at AKB Restaurant: A Sustainable Approach to Liquid Organic Fertilizer Production: Innovative Waste Management and Community Education at AKB Restaurant: A Sustainable Approach to Liquid Organic Fertilizer Production - balqis, solina; Tamami, Hibatu (Indonesian Journal of Community Empowerment and Service (ICOMES), 2025)
This community engagement initiative aimed to address organic waste management issues at the Angkringan Kampung Belimbing (AKB) restaurant by introducing innovations in liquid organic fertilizer (LOF) production and environmental education. The approach included initial observation, awareness sessions, hands-on LOF training using kitchen waste and Effective Microorganisms 4 (EM4), and evaluation through application on water spinach and shallot plants. Results indicated an increase in community understanding of circular economy principles and sustainable waste management. The LOF produced proved effective in enhancing plant growth and opened opportunities for eco-friendly local entrepreneurship. This program demonstrates that combining educational and practical strategies can significantly strengthen community awareness and capacity in independently managing organic waste in a sustainable manner.